INCARCERATION WITHOUT CONVICTION understanding the collateral consequences of pretrial detention. - Rabinowitz, Mikaela ([S.l.] : ROUTLEDGE, 2021)
IncarcerationWithout Conviction addresses an understudied fairness flaw in the criminal justice system. On any given day, approximately 500,000 Americans are in pretrial detention in the US, held in local jails not because they are considered a flight or public safety risk, but because they are poor and cannot afford bail or a bail bond. Over the course of a year, millions of Americans cycle through local jails, most there for anywhere from a few days to a few weeks. These individuals are disproportionately Black and poor. This book draws on extensive legal data to highlight the ways in which pretrial detention drives guilty pleas and thus fuels mass incarceration--and the disproportionate impact on Black Americans. It shows the myriad harms that being detained wreaks on people's lives and well-being, regardless of whether or not those who are detained are ever convicted. Rabinowitz argues that pretrial detention undermines the presumption of innocence in the American criminal justice system and, in so doing, erodes the very meaning of innocence.
OCLC-licensed vendor bibliographic record.
Keywords: Arrest -- United States; Presumption of innocence -- United States; Preventive detention -- United States; SOCIAL SCIENCE / Sociology / General